2012
DOI: 10.1177/0269215512453061
|View full text |Cite
|
Sign up to set email alerts
|

Can a six-week exercise intervention improve gross motor function for non-ambulant children with cerebral palsy? A pilot randomized controlled trial

Abstract: This study provides preliminary evidence that exercising on a bike or treadmill may provide short-term improvements in gross motor function for non-ambulant children with cerebral palsy. This needs to be tested in a large-scale randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0
20

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(119 citation statements)
references
References 22 publications
1
98
0
20
Order By: Relevance
“…An exercise therapy may consist of several types of training such as strength training, fitness training, static weight bearing and passive stretching ( 2 ). Though it has been proven to have its effect on muscular strength, volume and significantly increase motor ability of patients with CP, the type and duration of exercise therapy programme that should be prescribed to these patients remain unclear ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…An exercise therapy may consist of several types of training such as strength training, fitness training, static weight bearing and passive stretching ( 2 ). Though it has been proven to have its effect on muscular strength, volume and significantly increase motor ability of patients with CP, the type and duration of exercise therapy programme that should be prescribed to these patients remain unclear ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this case study is discussed in relation to other CP survivors and the maintenance of their functional capacities. Several studies indicate that exercise can increase muscular strength, gait speed, and stride length in children with CP [3,4,7,8], but little research has been conducted on adults with CP. Similarly, little is known about the psychological effects of exercise on adults with CP, such as their perception or self-belief to overcome exercise barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies show that exercise can improve motor skills and overall quality of life (QOL) in children with CP. For example, Bryant and colleagues showed that a six-week exercise intervention was able to improve gross motor function in children with CP [3]. In another study, researchers investigated the effects of constraint-induced movement therapy (CIMT) on hand skills and muscle recruitment of children with spastic hemiplegic CP [8].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, lower limb rehabilitation generally consists on gross motor activities involving repetitive and coordinated movements with both limbs (walking, cycling, etc. ), what sometimes does not require a conscious effort (Balemans et al, 2013;Bryant et al, 2012;Chen et al, 2012;Damiano, 2006;Leunkeu, Shepard & Ahmaidi, 2012;Mattern-Baxter et al, 2013), resulting in improvements in gait performance and gross motor ability (Baxter et al, 2013;Damiano, 1995;DiBiaso & Lewis, 2013;Johnson et al, 2011;Willoughby, Dodd, Shields & Foley, 2010). However, it is necessary to distinguish between the different types of training (strengthening, aerobic training) in order to provide a clearer picture of how each training modality may benefit people with CP.…”
Section: Discussionmentioning
confidence: 99%